POTENSI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAN FRAKSI N-HEKSAN BUAH JERUK PAMELO (Citrus maxima (Burm) Merr) ASAL KABUPATEN PANGKEP - Masdiana Tahir; Asriani Suhaenah; Yulinda Rahim (Faculty of Pharmacy, Universitas Muslim Indonesia, 2020)
Pomelo citrus (Citrus maxima (Burm) Merr) is a fruit plant that has the potential to be developed for health. Pomelo fruit contains lycopene, flavonoids and vitamin C which can provide antioxidant activity. The purpose of this study was to determine the potential antioxidant activity of ethanol extract and fraction of n-hexane of pomelo citrus using quercetin as a comparison. Extraction of pomelo citrus fruit using the maceration method with liquid-liquid fractionation using water and n-hexane (1: 3 v / v). Testing of antioxidant activity using the DPPH (1,1-Diphenyl-2-picrylhidrazil) method is based on the ability of the sample to capture DPPH free radicals which are characterized by purple to yellow discoloration and a decrease in the absorbance value of DPPH which has reacted with samples in certain concentrations. Absorbance measurements using a UV-Vis spectrophotometer at a wavelength of 514,942 nm. The results showed that the IC50 value of quercetin was 6.55 µg / mL which was a strong antioxidant, while the IC50 value of the ethanol extract of pomelo citrus fruit was 2882.26 µg / mL and IC50 value of the n-hexane fraction of pomelo orange was 3668,44 µg / mL which is a weak antioxidant category. Kata kunci : Antioxidants, Ethanol Extract, n-Hexane Fraction, Pomelo citrus (Citrus maxima (Burm) Merr